Academic Publication and Issues of the Day: U.S. Income Tax Paradigm - Service, Robert W.; Reburn, James P. (Archives of Business Research, 2016)
As academic researchers and American citizens during a most tempestuous Presidential election we have often been struck by the misinformation and misunderstanding of many of the issues of the day. It seems that the electorate world-wide are rationally ignorant and lazy and we in the academy do little to change that or even to represent a healthier paradigm. Perhaps it is because “it takes a lot of time to track down, organize, and analyze the data to answer even one small question well (p. 2). . . . [And, moreover,] When people don’t pay the true cost of something [or cannot understand the real costs], they tend to consume it inefficiently (p. 15). . . . [Finally,] if you ask the wrong question, you are almost guaranteed to get the wrong answer (p. 49).” These are the words of famed Freaknomics authors Levitt and Dubner in their latest work, Think like a Freak: How to Think Smarter about Almost Everything, (2014). In that work Levitt and Dubner challenge all of us, especially those of us that claim to be facilitating others toward a more effective life-time of work and contribution, to think more clearly toward developing real solutions for pressing issues. Those quotes lead us to the question of how does a “Freak” think? They think like a genuinely curious kid noticing new facts and views with few assumptions and expectations without overthinking: open to the obvious and the totally unexpected and everything in-between! With these thoughts in mind, the overall goal of this research is to produce an academic and practical exemplar starting point for U.S. Tax Code enhancements that could possibly be applied to world-wide tax policies (Areddy, 2015; Service and Loudon, 2013 and 2015; and Service, Loudon and Kariuki, 2014). Moreover, while developing our “straw-man” proposal we are demonstrating a “scholastic inquiry” being applied to developing a usefully suggested solutions for a contemporary and very important issues. We start with underlying assumptions that U.S. Federal Income Tax (FIT) as any governmental policy 1) must be understandable, 2) require no paid intermediaries, and 3) facilitate “automatic” evaluation of impacts for new governmental spending and financing proposals. This research should present a deep analysis of the how, who, why and what for addressing contemporary conundrums.